PENINGKATAN KEPEDULAN REMAJA PADA KEMAKMURAN MASJID AN-NASHR BINTARO, BANTEN - Abidin, Zainal; Shunhaji, Akhmad; Tasbih, Agus (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2023)
Increasing adolescent awareness of the prosperity of the An-Nashr Mosque in Bintaro, Banten. This research uses qualitative methods with data collection techniques in the form of interviews and observations. Participants in this research were Muslim teenagers who visited the An-Nashr Mosque. This research found that developing religious education and providing opportunities for teenagers to participate in developing mosque prosperity can increase teenagers' awareness of the Annashr Bintaro Banten mosque. Apart from that, giving tasks to teenagers in maintaining and developing the prosperity of mosques can form positive character and a caring attitude towards the surrounding environment, as well as help improve social relations between teenagers and the surrounding community. The involvement of teenagers in making the An-Nashr Bintaro Mosque prosperous can have a positive impact on the surrounding community and also on the personal development of teenagers, increasing religious activities in the mosque, training and developing various talents and skills of teenagers, as well as bringing benefits to the sustainability of social activities in the environment around. Therefore, it is recommended that there be two-way communication between mosque administrators and teenagers to find out their needs and desires, open up opportunities for teenagers to contribute to activities at the mosque, provide a clear understanding of the important role of mosques in everyday life, and create creative events that are interesting for teenagers to invite them to come to the mosque.